Recursos e adversidades no ambiente familiar de indivíduos usuários de crack - Seleghim, Maycon Rogério (2012)
Since the family plays a key role in the initiation and continuation of illicit drug use, the influence of the family environment in the use of crack by regular users or in those people dependent on the cocaine-derived drug is analyzed. Survey is cross-sectional, descriptive and features a series of cases, with a theoretical framework based on the General Systems Theory, particularly a Genogram to identify multigenerational family issues associated with the use of illicit drugs. The study was conducted in Maringá PR Brazil, and the cases investigated, regardless of county of origin, hailed from a Therapeutic Community (TC) in the northwestern region of the state of Paraná. The sample consisted of 20 crack users who were classified as habitual or functionally dependent males, aged over 18, treated at the TC during May 2011. Their families were also surveyed through a chosen family member as informant. In fact, 15 family members were also investigated within the sample, characterized by criteria for functionality of drug use. Half-structured surveys were employed for data collection. These comprised space for the drawing of the Genogram - User Survey and Family Survey, a questionnaire for the social and economical conditions of the families and a field diary. Individual interviews were undertaken focusing on the history of the illicit drug users and their family relationships. The latter helped in the construction of a two-generation Genogram. Whereas quantitative data were submitted to descriptive statistics, qualitative data were analyzed by thematic content analysis. Genograms were inserted in Power Point program and analyzed in a process similar to content analysis. Most users were in the 20 - 39 years age bracket, single or separated / divorced, with low schooling, unemployed. Drug use pattern was characterized by frequency, with an initial onset of licit and illicit drugs when they were young. Their life trajectory confirmed an escalation in the use of psychoactive substances, starting from tobacco and / or alcohol and ending with crack. The family informants were mostly mothers, aged 19 to 62 years, married, with children, low schooling, Catholics and employees. Most families belonged to the economic classes C and B, with religious practice, users of the government medical care (SUS) and indicated the family lunch as their most frequent recreational activity. The fifteen Genograms analyzed included 378 family members, with an average of 25.2 members. Family frames were diverse: nine were nuclear families, four were single parent families, two community families. All families had at least a harmonious relationship with a family member; 11 had distant relationships with maternal or paternal grandparents and uncles; seven had a conflicting relationship, especially with daughter-in-law, brother, children, grandchildren, spouse and former spouse. Fourteen families revealed a history of drug use and eight had a history of illicit drug use, particularly marijuana, cocaine and crack. Ninety-one people were identified as consumers of alcohol and / or tobacco. Deficiency in parental support, a family culture in drug use and family conflicts were among the determining factors for drug use. The families studied had several issues which were unfavorable to the family environment. In fact, they facilitated the use of illicit drugs, especially crack. Analysis of Genograms confirmed multigenerational reproductive behaviors associated with illicit drug use through the influence of cultural aspects, beliefs and family values.